Nonparametric M-estimation with long-memory errors - Jan Beran; Sucharita Ghosh; Philipp Sibbertsen (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2000)
We investigate the behavior of nonparametric kernel M-estimators in the presence of long-memory errors. The optimal bandwidth and a central limit theorem are obtained. It turns out that in the Gaussian case all kernel M-estimators have the same limiting normal distribution. The motivation behind this study is illustrated with an example.
Keywords: 519; Zeitreihenanalyse; Nichtparametrisches Verfahren; Theorie; Statistischer Fehler